2021
DOI: 10.51528/rp.vol8.id2189
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgos sociales que intervienen en la ocurrencia de accidentes de tránsito con vehículos livianos

Abstract: El transporte a nivel social es un elemento de elevada importancia para lograr la movilidad de los individuos y el traslado de recursos, al desarrollar esta actividad no son pocos los factores de riesgos que conllevan a la ocurrencia de accidentes con los respectivos perjuicios en el ámbito socioeconómico y las lamentables lesiones o pérdidas de vidas humanas. Con el propósito de realizar una revisión descriptiva de los estudios compilados enfocados a los factores de riesgos sociales para que se produzcan acci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In this context, it is necessary to implement restraint devices and other safety elements in vehicles to ensure adequate protection. In addition, special attention should be paid to access and fire risk (Rivera & Vargas, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, it is necessary to implement restraint devices and other safety elements in vehicles to ensure adequate protection. In addition, special attention should be paid to access and fire risk (Rivera & Vargas, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous work Chávez et al [8], observed that Covid-19 pandemic was involved in the change in the frequencies of the causes of accidents, with this the trends and projections also present variations [9]. The author intends a characterize traffic accidents during 2015-2020.…”
Section: Introductionmentioning
confidence: 98%